Development of the Scalp Hair Assessment PRO™ measure for alopecia areata. (26th May 2020) - Wyrwich, K.W.; Kitchen, H.; Knight, S.; Aldhouse, N.V.J.; Macey, J.; Nunes, F.P.; Dutronc, Y.; Mesinkovska, N.; Ko, J.M.; King, B.A.
Summary: Background: Valid patient‐reported outcome (PRO) measures are required to evaluate alopecia areata (AA) treatments. Objectives: To develop a content‐valid and clinically meaningful PRO measure to assess AA scalp hair loss with scores comparable with the five‐response‐level Alopecia Areata Investigator Global Assessment (AA‐IGA™). Methods: A draft PRO measure was developed based on input from 10 clinical experts in AA. The PRO measure was cognitively debriefed, modified and finalized through two rounds of qualitative semistructured interviews with patients with AA who had experienced ≥ 50% scalp hair loss. Data were thematically analysed. Results: Adults (round 1: n = 25; round 2: n = 15) and adolescents aged 15–17 years (round 1: n = 5) in North America participated. All patients named scalp hair loss as a key AA sign or symptom. Patients demonstrated the ability to self‐report their current amount of scalp hair using percentages. In round 1 not all patients interpreted the measurement concept consistently; therefore, the PRO was modified to clarify the measurement concept to improve usability. Following modifications, patients in round 2 responded without difficulty to the PRO measure. Patients confirmed that they could use the five‐level response scale to rate their scalp hair loss: no missing hair, 0%; limited, 1–20%; moderate, 21–49%; large, 50–94%; nearly all or all, 95–100%. Almost all patients deemed hair regrowth resulting in ≤ 20% scalp hair loss a treatment success. Conclusions: The Scalp Hair Assessment PRO™ is a content‐valid, clinically meaningful assessment of distinct gradations of scalp hair loss for evaluating AA treatment for patients with ≥ 50% hair loss at baseline. Abstract : What is already known about this topic? Assessing patient‐reported outcomes is critical in patient‐focused drug development. The patient perspective on their own signs, symptoms and unmet needs provides a key clinical trial data source for evaluating treatment outcomes. Clinically meaningful and content‐valid patient‐reported outcome (PRO) measures are required to collect these data in alopecia areata (AA) clinical trials. What does this study add? This study developed a content‐valid PRO measure for patients with AA to self‐report the status of their scalp hair loss. This novel PRO measure allows scalp hair loss to be characterized into clinically meaningful gradations across the range of 0–100% missing scalp hair. What are the clinical implications of this work? The Scalp Hair Assessment PRO™ provides a new clinical outcome assessment of AA scalp hair loss for use in both clinical trials to evaluate the efficacy of novel treatments and in clinical practice to obtain a patient‐centred perspective on the key sign and symptom of AA. With corresponding response options to the newly developed Alopecia Areata Investigator Global Assessment (AA‐IGA™), clinician and patient assessments are comparable to elucidate any perceived differences between respondents. Linked Comment: Rencz. Br J Dermatol 2020; 183 :986–987 .